Glucose transport in a kinaseless Saccharomyces cerevisiae mutant. - Lang, J M (1987)
Wild-type Saccharomyces cerevisiae organisms contain three kinases which catalyze the phosphorylation of glucose: two hexokinase isozymes (PI and PII) and one glucokinase. Glucose transport measurements for triple-kinaseless mutants, which lack all three of these kinases, confirm that the kinases are involved in the low apparent Km transport process observed in metabolizing cells. Thus kinase-positive cells containing one or more of the three kinases exhibit biphasic transport kinetics with a low apparent Km (1 to 2 mM) and high apparent Km (40 to 50 mM) component. Triple-kinaseless cells, however, exhibit only the high apparent Km component of kinase-positive cells (60 mM). Kinetic analysis of glucose transport in the triple-kinaseless cells shows that glucose is transported by a facilitated diffusion process which exhibits trans-stimulated equilibrium exchange and influx counterflow.